Malaysian youth’s receptivity towards code-switching in Malay drama television series / Muriatul Khusmah Musa and Ting Su-Hie - Musa, Muriatul Khusmah; Ting, Su-Hie (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
As a reflection of the multilingual characteristics of the Malaysian speech community, some Malaysian television series have incorporated use of code-switching in their shows. This study examined whether Malaysian youths' receptivity towards code-switching in Malay drama television series is linked to their own tendency to code-switch. A short video clip of a Malay drama television series with code-switching was shown before the university students filled in a questionnaire on their frequency of code-switching in daily life, and reasons for acceptability and unacceptability of code-switching in Malay drama television series. The results from 141 university participants indicated that Malay students code-switched more frequently than non-Malay students and they are also more receptive towards code-switching in Malay drama television series. However, a majority of the participants (Malay and non-Malay) found code-switching in Malay drama television series unacceptable, but their objections were not on the grounds that code-switching would adversely affect their ability to learn and speak English and Bahasa Melayu (BM). They also did not believe that code-switching has implications on their image, pro-Western stance and religious fervour. The Malay and non-Malay participants diverged in their views on code-switching and patriotism – 20% of participants who found code-switching in Malay drama television series acceptable did not do so as a result of associating code-switching with educatedness, sophistication, modernity, racial tolerance, 1Malaysia image and potential for BM to develop. The results suggest that code-switching in Malay drama television series is seen as an extension of communicative behaviour in daily life.